Determination of Eating Attitude and Life Satisfaction in Patients with Type 2 Diabetes Mellitus: A Cross-Sectional Study - Güldane Yaşdal; Arzu Yıldırım (Sakarya Üniversitesi Holistik Sağlık Dergisi)
Objective: Type 2 diabetes mellitus is a severe, chronic metabolic disease. Since mental or behavioral problems accompanying physical diseases negatively affect the patient's adaptation, well-being, mortality and morbidity, it is essential to evaluate these problems. The aim of the study was to determine eating attitudes and life satisfaction in patients with type 2 diabetes mellitus. Method: This cross-sectional study consisted of 130 patients who were hospitalized at the internal medicine and wound care services in Sakarya Training and Research Hospital and who met the inclusion and exclusion criteria. The data were collected by face-to-face interviews using the Patient Descriptive Questionnaire, Eating Attitude Test-40 and Satisfaction with Life Scale.Results: The prevalence of probable eating disorder among the patients was 46.9% (n¬=61) and their perception of life satisfaction was above moderate. Additionally, it was determined that there was a significant difference between the mean of the Satisfaction with Life Scale score according to income and perception of health status, and between the mean of the Satisfaction with Life Scale score and possible eating disorder according to the place of residence (p<0.001).Conclusion: In this study, approximately half of the patients with type 2 diabetes mellitus are at risk for eating disorders and their perception of life satisfaction was above moderate. Healthcare professionals must provide individual-centered.